Taschengeld und Sparverhalten bei Grundschulkindern: eine empirische Untersuchung in Nordwestdeutschland - Nicole Dubbert; Rainer Hufnagel (Westfälische Wilhelms-Universität Münster, Institut für Ökonomische Bildung (IÖB), 2006)
This working paper presents the results of a survey of 330 schoolchildren from three primary schools in small rural towns in North-Rhine Westfalia and Lower Saxony. The questions dealt with pocket money and savings behaviour and the data related to two main issues. Firstly, a measure was made to the extent to which the investigated families apply the central recommendations of pocket money pedagogy. Secondly, the data was considered in the context of the established attitudinal-behavioural models. The results reveal that approximately 80 % of the children receive pocket money regularly. The average weekly amount is EUR 2.29, with a standard deviation of EUR 1.61. Within the attitude-behaviour-framework, a relationship was proven between the perceived behavioural control of the children and their ability to come out with the pocket money. This results supplements and confirms analogous findings from health didactics, in which strengthening the self esteem of children has emerged a central pillar of prevention of unhealthy behaviour.
Keywords: A21; D14; D31; I22; 330; Schüler; Kinder; Sparen; Deutschland